FACTORS THAT INFLUENCE STUDENT INTEREST IN CHOOSING THE SPAN-PTKIN PATHWAY FOR MATHEMATICS EDUCATION STUDY PROGRAMS AT UIN SJECH M. DJAMIL DJAMBEK BUKITTINGGI - Kuntum Khaira A.M, Kuntum Khaira A.M (BiCED Proceeding, 2024)
This study aims to analyze the factors that influence student interest in choosing the SPAN-PTKIN pathway in the Mathematics Education Study Program at UIN Sjech M. Djamil Djambek Bukittinggi. Interest refers to a person's interest, desire, attention, and involvement in something or activity without being told or forced. That is, when someone is interested in something, his behavior is based on inner impulse, not coercion. The research method used is qualitative, with purposive sampling technique. The number of samples of this study were 6 active students who had just entered in the 2024/2025 academic year in the Mathematics Education Study Program class A. Data were obtained through in-depth interviews with students, then analyzed thematically to identify the factors that played a role in the decision to choose the path. The results showed that students' interest was influenced by several main factors, such as the reputation of the study program, career prospects, family support, and the accessibility and ease of the registration process through the SPAN-PTKIN pathway. The findings are expected to be taken into consideration by the university in improving its promotion and admission strategies in the future.